Caligus lini n.sp., a new caligid (Copepoda, Siphonostomatoida) parasitic on the brilliant pomfret Eumegistus illustris Jordan & Jordan (Perciformes, Bramidae) of Taiwan - Ho, Ju-Shey; Cheng, Yu-Rong (Zootaxa, 2016)
Caligus lini n.sp., a new species of caligid copepod parasitic on the gill rakers and caudal fin of the brilliant pomfret, Eumegistus illustris Jordan & Jordan (Perciformes, Bramidae), is described from fish caught off Tai-Dong, Taiwan. The new species differs from its congeners by its possession of the following, unique combination of features: (1) middle two elements at the tip of leg 1 simple (without accessory process), (2) innermost element shortest and smallest of the four terminal elements on leg 1, (3) leg 4 exopod with an armature formula of I,III, and (4) complex leg 5 represented by 2 seta-bearing processes, a simple anterior process tipped with 1 plumose seta and quadripartite posterior process carrying 3 setae (1 simple and 2 plumose). The new species differs from its closest congener, Caligus tylosuri (Rangnekar, 1956), in the structure of the middle two elements (simple without carrying accessory process) at the tip of leg 1 and a quadripartite (instead of tripartite) posterior process on leg 5.